Development of Oxadiazole-Based ODZ10117 as a Small-Molecule Inhibitor of STAT3 for Targeted Cancer Therapy - Kim, Byung-Hak; Lee, Haeri; Song, Yeonghun; Park, Joon-Suk; Gadhe, Changdev G.; Choi, Jiwon; Lee, Chung-Gi; Pae, Ae Nim; Kim, Sanghee; Ye, Sang-Kyu (MDPI, 2019)
Persistently activated STAT3 is a promising target for a new class of anticancer drug development and cancer therapy, as it is associated with tumor initiation, progression, malignancy, drug resistance, cancer stem cell properties, and recurrence. Here, we discovered 3-(2,4-dichloro-phenoxymethyl)-5-trichloromethyl-[1,2,4]oxadiazole (ODZ10117) as a small-molecule inhibitor of STAT3 to be used in STAT3-targeted cancer therapy. ODZ10117 targeted the SH2 domain of STAT3 regardless of other STAT family proteins and upstream regulators of STAT3, leading to inhibition of the tyrosine phosphorylation, dimerization, nuclear translocation, and transcriptional activity of STAT3. The inhibitory effect of ODZ10117 on STAT3 was stronger than the known STAT3 inhibitors such as S3I-201, STA-21, and nifuroxazide. ODZ10117 suppressed the migration and invasion, induced apoptosis, reduced tumor growth and lung metastasis, and extended the survival rate in both in vitro and in vivo models of breast cancer. Overall, we demonstrated that ODZ10117 is a novel STAT3 inhibitor and may be a promising agent for the development of anticancer drugs.
Keywords: TRANSCRIPTION 3; SIGNAL TRANSDUCER; BREAST; ACTIVATION; CELLS; SUPPRESSION; AMIDOXIMES; FUTURE; AXIS